An Integrated Approach to the Conceptualisation and Measurement of Social Cohesion - Bujar Aruqaj (Social Indicators Research, 2023)
The core sociological subject of 'social cohesion' (hereafter SC) has re-emerged as a key concept in the social sciences. On the one hand, SC is thought to be influenced by a society's degree of inequalities and the quality of its welfare state. On the other hand, SC is thought to be instrumental in its own right to other factors such as economic growth, institutional quality, and individual well-being. In recent years, a few attempts have been made to measure SC empirically. Many current indices have not been sufficiently theoretically substantiated, and do not consider the importance of different 'social levels' when explaining and measuring SC as both cause and effect of other correlates. Very often, SC is simply defined as a 'social quality' or a quality of a collective. As a result, measures are often aggregate macro-indices leading to a loss of the information base of any social 'units' below the macro-societal-level. Contributing to this important methodological debate, this paper provides a conceptual reformulation of SC. Hence, when assessing SC based on a multi-dimensional index, it is insightful and feasible to evaluate both its internal variation as well as its holistic validity. In fact, it is proposed that these two aspects of measurement stand in direct relationship to one-another. The paper starts out with a discussion of SC as a 'social fact' in the Durkheimian sense. In addition, three bridging propositions on the measurement of SC are advanced: (a) SC as outcome or consequence at the level of individual attitudes and orientations ('micro'); (b) SC as degree of dissimilarity and presence of latent conflict within a society at the level of salient social categories ('meso'), and (c) SC as predictor, social determinant and hence antecedent at the societal-level ('macro'). Using all rounds of the European Social Survey with a very large sample size, the advantages of this approach are illustrated by singling-out the important link between socio-economic inequalities, social cohesion and individual subjective well-being in a path of action.
Keywords: 300; Social cohesion; Social integration; Social trust; Social inequalities; Latent conflict; Europe; Social cohesion index; Subjective well-being; Regional cohesion